Stabilization of oxygen vacancy ordering and electrochemical-proton-insertion-and-extraction-induced large resistance modulation in strontium iron cobalt oxides Sr(Fe,Co)O y - Yosuke Isoda; Thanh Ngoc Pham; Ryotaro Aso; Shuri Nakamizo; Takuya Majima; Saburo Hosokawa; Kiyofumi Nitta; Yoshitada Morikawa; Yuichi Shimakawa; Daisuke Kan (Nature Communications)
Abstract Electrochemically inserting and extracting hydrogen into and from solids are promising ways to explore materials’ phases and properties. However, it is still challenging to identify the structural factors that promote hydrogen insertion and extraction and to develop materials whose functional properties can be largely modulated by inserting and extracting hydrogen through solid-state reactions at room temperature. In this study, guided by theoretical calculations on the energies of oxygen reduction and hydrogen insertion reactions with oxygen-deficient perovskite oxides, we demonstrated that the oxygen vacancy ordering in Sr(Fe1−x Co x )O y (SFCO) epitaxial films can be stabilized by increasing the Co content (x ≥ 0.3) and revealed that it plays a key role in promoting proton accommodation into the SFCO lattice. We also show that the electrical resistance of SFCO films can be reversibly modulated by electrochemical proton insertion and extraction, and the modulation exceeds three orders of magnitude for Sr(Fe0.5Co0.5)O2.5 epitaxial films. Our results provide guidelines for controlling material properties through the insertion and extraction of hydrogen and for designing and exploring hydrogen-insertion materials.